PEMBERDAYAAN PENGRAJIN TENUN IKAT LAKI-LAKI DI KELURAHAN PALAMARUNG KABUPATEN SUMBA TIMUR - Niha, Desinta May; Klau, Erni Raster; Selly, Frans Kristian (Education For All, 2024)
Abstract This research is motivated by the problem that men's empowerment can also be realized through active participation in the wider community facilitated by empowerment actors. Men in Palamarung M1 Subdistrict (20 years old) are involved in informal sector economic activities as weaving craftsmen. This research aims to find out the process of empowering male ikat weaving craftsmen and what are the supporting and inhibiting factors as a male ikat weaving craftsman This research method uses qualitative methods and the research location is in Palamarung Village, East Sumba Regency. The subjects in this research were ikat weaving craftsmen, parents, village heads, school principals and students. Data collection uses interview techniques, observation and documentation studies. Data analysis techniques include data collection, data reduction, data presentation, and conclusion. The results of the research show that M1 is a male Ikat Weaving Craftsman in Palamarung Village, East Sumba Regency. Awareness actions carried out by M1 include approaching schools about the importance of preserving ikat culture and conducting outreach to students to take part in extracurricular activities on ikat weaving as an extracurricular of interest. As well as grouping students based on gender in preparing weaving materials and tools. In the Transformation stage, M1 prepares materials and collaborates with the school to create extracurricular schedules and study agreements. Apart from that, the sales and promotion process is carried out through social media. The stage of student independence is combined in a class and group between male and female students.